ENRICHMENT OF α-( ALPHA) LINOLENIC ACID OF BASIL SEED OIL, Ocinum Basillium L. BY FRACTIONAL CRYSTALIZATION AND CRYSTALIZATION IN UREA INCLUSION COMPLEXES - Warsito Warsito; Jumina Jumina; Chairil Anwar; Rurini Retnowati; Ahmad Ghanaim; Suleman Duengo (Indonesian Journal of Chemistry, 2011)
Enrichment of α-(alpha) linolenic acid (ALA) of basil seed oil, Ocinum basilicum L. can be done by fractional crystalization and crystalization of fatty acid in urea inclusion complexes (UIC) methods. In this research, the ALA of fatty acid of basil seed oil was fractionated by fractional crystallization in methanol solution at -3, -13 and -25 °C and by crystallization in urea solution (ratio 1:2) at 4, 2, -6 and -8 °C. The ALA percentages were analyzed by GC and GC/MS. The results showed that percentage of ALA obtained from fractional crystallization at -25 °C increase from 65.16 to 91.40, and acquired from UIC is 98.8 at 2 °C